Can media and communication researchers turn the present challenges of research impact and interdisciplinarity into future opportunities?. (November 2016) - Tsatsou, Panayiota
This statement critically reflects on two of the main challenges in media and communication research: the disputed societal value and impact of media and communication research and the shortage of interdisciplinary research in the field. The statement makes concrete suggestions about how these two 'deficiencies' can be turned into opportunities, with one paving the way for encountering and solving the other. At the same time, it acknowledges the existence of the following two caveats: first, the notion of interdisciplinarity has not yet been sufficiently explored or even comprehended among researchers across disciplines, and its future shape and directions cannot be foreseen; second, impact itself is time- and context-relative and researchers must be in tune with broader developments in the real-life world to sense the changes happening and the emerging areas of impact that require their attention.